A multi-resolution fast filter bank for spectrum sensing in military radio receivers - Smitha, Kavallur Gopi (2013)
In this paper, we propose a multi-resolution filter bank (MRFB)-based on the fast filter bank design for multiple resolution spectrum sensing in military radio receivers. The proposed method overcomes the constraint of fixed sensing resolution in spectrum sensors based on conventional discrete Fourier transform filter banks (DFTFB). The flexibility in realizing multiple sensing resolution spectrum sensor is achieved by suitably designing the prototype filter and efficiently selecting the varying resolution subbands without hardware re-implementation. Design examples show that the sensing performance of proposed MRFB is comparable to that of conventional fixed resolution DFTFB. The complexity comparison shows that the proposed MRFB architecture has a gate count reduction of 36.5% over the DFTFB. The proposed MRFB architecture achieves an average power reduction of 20.8% over DFTFB.